2017
DOI: 10.1038/s41467-017-01358-x
|View full text |Cite
|
Sign up to set email alerts
|

Mutational signatures reveal the dynamic interplay of risk factors and cellular processes during liver tumorigenesis

Abstract: Genomic alterations driving tumorigenesis result from the interaction of environmental exposures and endogenous cellular processes. With a diversity of risk factors, liver cancer is an ideal model to study these interactions. Here, we analyze the whole genomes of 44 new and 264 published liver cancers and we identify 10 mutational and 6 structural rearrangement signatures showing distinct relationships with environmental exposures, replication, transcription, and driver genes. The liver cancer-specific signatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
272
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(303 citation statements)
references
References 51 publications
(76 reference statements)
19
272
5
2
Order By: Relevance
“…Like in resected HCC BCLC 0/A, most mutations in advanced HCC were related to mutational signatures 4 (polycyclic aromatic hydrocarbon exposure), 5 (clock-like, related to age), and 16 (liver hallmark, increased by alcohol consumption), ubiquitous in liver cancers. (17) Three samples from African migrants displayed a high mutation load related to signature 24 (aflatoxin B1 exposure; Fig. 5C,D; Supporting Fig.…”
Section: Genetic Landscape Of Advanced Hccmentioning
confidence: 95%
“…Like in resected HCC BCLC 0/A, most mutations in advanced HCC were related to mutational signatures 4 (polycyclic aromatic hydrocarbon exposure), 5 (clock-like, related to age), and 16 (liver hallmark, increased by alcohol consumption), ubiquitous in liver cancers. (17) Three samples from African migrants displayed a high mutation load related to signature 24 (aflatoxin B1 exposure; Fig. 5C,D; Supporting Fig.…”
Section: Genetic Landscape Of Advanced Hccmentioning
confidence: 95%
“…By contrast, the signature was in <1% of HCCs from Japan (17,18) and France. (19) Interestingly, among the US HCCs, (20) Asian patients had higher detection rates of the AA signature (24 [15%] of 160 HCCs) than non-Asian patients ( Table 1). In addition, we noticed that 11 (11%) of 103 ICCs from China (21) and 29 (24%) of 121 cHCC-ICCs from the Asian region (mainland China, Singapore, and Japan) (22) contained the AA signature (Table 1).…”
Section: Aa Exposure Is Closely Associated With Liver Cancers From Chmentioning
confidence: 99%
“…COSMIC signature 24 was found to be an aflatoxin B1‐associated signature, and was more frequent in African cases with significant enrichment of a somatic TP53 p. Arg249Ser mutation, which is a typical mutation of aflatoxin B1‐exposed HCC. Letouzé et al further analyzed WGS of European HCC cases and identified 10 mutational signatures (COSMIC signatures 1, 4, 5, 6, 12, 17, 16, 22, 23, and 24). Of note, they affirmed a significant association between COSMIC signature 16 and epidemiological backgrounds such as male gender, alcohol intake, and tobacco consumption.…”
Section: Mutational Signatures In the Hcc Genomementioning
confidence: 99%
“…Letouz e et al 23 8 Although the frequency of AA-associated HCC is low in Japan and Western countries, exposure to AA or their derivatives would play an important role in HCC globally, especially in East Asia, implying substantial opportunities for prevention and intensive screening of HCC in these endemic areas.…”
Section: Structural Rearran Gements An D Virus Integration In H Ccmentioning
confidence: 99%